Foreign body ingestion: distribution, its complication and management - Sharma, Kalpana; Pyrbot, Kune S.; Sava, Nasimus (International Journal of Research in Medical Sciences, 2024)
Background: Foreign body ingestion can lead to severe complications, especially if the object becomes lodged in the oesophagus. Complications may include perforation, obstruction, and secondary infections. Early diagnosis using soft tissue neck and chest radiographs can help determine the location, type of foreign body and any associated abscess formation. In cases with complications, the primary treatment involves intravenous antibiotics followed by removal of foreign body. Methods: This prospective observational study was conducted in the Department of Otorhinolaryngology and Head and Neck Surgery at Gauhati Medical College and Hospital, Guwahati. A total of 144 patients with foreign body ingestion treated in our hospital from September 2023 to August 2024 were included. Each patient underwent a thorough clinical assessment and radiographs of the soft tissue neck, chest, and abdomen (both lateral and anteroposterior views). A computed tomography (CT) scan was performed, if necessary, to confirm the presence of foreign body and to identify any potential complications. Results: Among the 144 patients, 18 developed complications related to foreign body ingestion ranging from 6-60 years old with a male-to-female ratio of 2:1. The most frequent complication was retropharyngeal abscess, followed by oesophageal obstruction, respiratory obstruction, and oesophageal tear. Out of the 18 patients, one patient expired as a result of complications. Conclusions: Foreign body ingestion can cause serious complications such as oesophageal obstruction, mucosal laceration and perforation, airway obstruction, and infections. Prompt identification and intervention are essential to manage these complications effectively and to reduce morbidity and mortality in affected patients.